Microbiota of female genital tract - functional overview of microbial flora from vagina to uterine tubes and placenta - Liptáková, A; Čurová, K; Záhumenský, J; Visnyaiová, K; Varga, I (Physiological research, 2022)
Microorganisms and eukaryotic human cells coexist in synergistic relationships in nearly every niche of the human body. The female genital tract consisting of the vagina, uterus with its cervix and endometrium, uterine tubes and ovaries - harbors its own typical microbiota, which accounts for 9 % of the total bacterial population in females. To this organ system, we also assigned the microbiome of the placenta, which has not been studied much until now. Among the spectrum of microbial species, the female genital tract is mainly dominated by Lactobacillus species, which are considered to be one of the simplest yet most important microbial communities. However, this relationship between macro- and micro-organisms seems to have a number of physiological functions, e.g., the vaginal and cervical microbiota have unique impact on reproductive health. The aim of this review was to provide current view on female genital tract microbiota and its role in reproductive health. We describe in detail the association of vaginal or tubal epithelium with microbiota or the role of microbiota in normal placental function.
Keywords: mikrobiota; Fallopian Tubes; Vagina; ženské pohlavní orgány; vagina; placenta; ženské pohlaví; Humans; Placenta; Pregnancy; Female; Microbiota; těhotenství; vejcovody; lidé; Genitalia, Female